Extreme minimum temperatures in the Great Lakes region of the United States: A climatology with implications for insect mortality. (9th November 2021) - Kiefer, Michael T.; Andresen, Jeffrey A.; McCullough, Deborah G.; Baule, William J.; Notaro, Michael
Abstract: Winter‐season extreme minimum temperatures may play a major role in limiting population growth and spread of the hemlock woolly adelgid (HWA) ( Adelges tsugae Annand) (Hemiptera: Adelgidae), an invasive sap‐feeding insect that has caused extensive mortality of hemlock trees ( Tsuga spp.) in many eastern United States (US) forests. This atypical insect feeds throughout the winter but populations can sustain high mortality when winter‐season extreme minimum temperatures drop below −20 to −30°C. Detection of HWA in Michigan during 2015 motivated interest in HWA winter survival in the US Great Lakes region. Here, we used the parameter‐elevation regressions on independent slopes model (PRISM) gridded daily minimum temperature dataset to construct a 1981–2018 climatology of extreme minimum temperatures in the Great Lakes region, the first such effort for this region. Metrics examined include absolute and mean annual extreme minimum temperatures (defined as the lowest daily minimum temperature during the study period and the study‐period mean lowest daily minimum temperature during each calendar year, respectively), and the frequency of daily minimum temperatures below −20 and −30°C. Minimum temperature patterns we identified support the following two hypotheses: first, proximity to water, surface elevation and latitude are the principal controls for extreme minimum temperatures in the Great Lakes region; second, the modifying influence of the relatively warm Lake Michigan serves to protect locations within about 10–25 km of the lakeshore from severe and potentially lethal temperatures for HWA. Analysis of projected minimum temperatures at the end of the 21st century (2080–2099) reveals a range of HWA distribution expansion scenarios. Although the original motivation for this study arose from interest in potential HWA mortality, a climatological study of extreme minimum temperatures has potentially broad relevance to, for example, human health and safety and forest ecology. Abstract : We used the parameter‐elevation regressions on independent slopes model (PRISM) gridded daily minimum temperature dataset to construct a 1981–2018 climatology of extreme minimum temperatures in the US Great Lakes region, with potential application to insect mortality [specifically, hemlock woolly adelgid (HWA) mortality]. This figure depicts contoured maps of mean annual extreme minimum temperature. The presence of temperatures above −20°C near and downwind of the Great Lakes suggests that these areas are more susceptible to HWA incursions than inland areas.